2009
DOI: 10.1124/dmd.109.027680
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulate CYP3A4 Expression via Direct and Indirect Targeting

Abstract: ABSTRACT:CYP3A4 metabolizes many drugs on the market. Although transcriptional regulation of CYP3A4 is known to be tightly controlled by some nuclear receptors (NR) including vitamin D receptor (VDR/ NR1I1), posttranscriptional regulation of CYP3A4 remains elusive. In this study, we show that noncoding microRNAs (miRNAs) may control posttranscriptional and transcriptional regulation of CYP3A4 by directly targeting the 3-untranslated region (3UTR) of CYP3A4 and indirectly targeting the 3UTR of VDR, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
195
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(205 citation statements)
references
References 29 publications
4
195
2
4
Order By: Relevance
“…Considerable efforts have been made recently to elucidate the roles of specific miRNA species in regulating DME expression. MiRNAs have been shown to affect the expression of many DMEs, including CYP1B1 [18],CYP2E1 [19], CYP3A4 [20] and SULT1A1 [21]. In the case of CYP2C19, two miRNA binding sites were identified within its 3′-UTR that interacted with miR-103 or miR-107 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made recently to elucidate the roles of specific miRNA species in regulating DME expression. MiRNAs have been shown to affect the expression of many DMEs, including CYP1B1 [18],CYP2E1 [19], CYP3A4 [20] and SULT1A1 [21]. In the case of CYP2C19, two miRNA binding sites were identified within its 3′-UTR that interacted with miR-103 or miR-107 [22].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the CYP3A4 protein level showed a significantly positive correlation with the CYP3A4 mRNA level indicating that the transcriptional regulation mainly contributes to the expression. Although we didn't examine CYP3A4 further, Pan et al (2009a) subsequently reported that CYP3A4 protein in LS180 and human pancreas cancer-derived PANC1 cells was decreased by the overexpression of miR-27b, accompanied by a decrease of the CYP3A4 mRNA level. A limitation of their study may be that the conclusion was drawn from only an overexpression study.…”
Section: Cyp3a4 and Pregnane X Receptor (Pxr)mentioning
confidence: 98%
“…Pan et al (2009a) have reported, using LS180 and PANC1 cells, that overexpression of miR-27b decreased the expression of VDR. Ji et al (2009) have reported, using rat hepatic stellate cells, that the inhibition of miR-27a and miR-27b increased the expression of retinoid X receptor α (RXRα), a heterodimer partner of various nuclear receptors such as PXR, VDR, CAR, PPAR, farnesoid X receptor, and liver X receptor.…”
Section: Lin Et Al (2009) Have Reported Using Mouse Embryonic Fibrobmentioning
confidence: 99%
“…In many laboratories, miRNAs have been shown to affect DMEs related with paracetamol metabolism (13)(14)(15)(16)(17)(18)(19). For example, miR-27b and miR-378 regulate paracetamol oxidation enzyme CYP3A4 and CYP2E1, respectively (13,14). Research on miRNAs regulation of phase II enzymes was limited to SULT1A1 (paracetamol sulfation enzyme), GSTP1 (NAPQI conjugation enzyme) and UGT1A (paracetamol glucuronidation enzyme) (15)(16)(17).…”
mentioning
confidence: 99%
“…In many laboratories, miRNAs have been shown to affect DMEs related with paracetamol metabolism (13)(14)(15)(16)(17)(18)(19). For example, miR-27b and miR-378 regulate paracetamol oxidation enzyme CYP3A4 and CYP2E1, respectively (13,14).…”
mentioning
confidence: 99%